Tube introducer and modified Celestin tube for use in palliative intubation of oesophagogastric neoplasms at fibreoptic endoscopy. Issue 7 (July 1978) - Atkinson, M; Ferguson, R; Parker, G C
Abstract : A new method for palliative intubation of inoperable neoplasms at or near the cardia is described. A guidewire is passed through the stricture, which is dilated using Eder Puestow metal olive dilators. The tube to be inserted is mounted on an introducer, which grips its distal end from inside, and is slid into position along the wire under radiological control. Twenty-five patients have been intubated with one death directly resulting from the procedure. The method provides a simple and relatively safe means of relieving dysphagia and improving nutrition.